O papel modulatório do ferro sobre a resposta imune na Leishmaniose Visceral - Nascimento, Paulo Ricardo Porfirio do (2012)
Iron is an essential element for many cellular functions, including the immune response against intracellular pathogens. In this study, we aimed evaluate the effect of iron on IRP2, IFN-γ, TNF-α, IL-6, IL-10, MIG and IP10 expression in PBMC and assess the effect of the spleen parasite load on the expression of these genes in the spleen of L. infantum naturally infected dogs. Blood sample from 7 DTH+ donor was collected and PBMC was obtained. The cells were cultivated in absence (iron chelator desferroximane, DFO 10 μM supplemented media) or in presence of iron (hemin 6 mM) for 1 h, followed by stimulation with Leishmania infatum antigen for 4 h. 44 dog spleen samples were obtained and parasite load in this organ was determinate by qPCR. Gene expression was analyzed by qPCR and cytokine production quantified by flow cytometry. In antigen stimulated cells, genes involved in immune response are significantly more expressed in presence of iron. T CD4+ and TCD8+ lymphocytes produces IFN-γ, TNF-α and IL-10 possibly in iron dependent pathway. Monocytes antigen stimulated reduced TNF-α, IL-6 and IL-10 production in presence of iron. We found spleen of infected dogs IRP2 expression increases according to parasite load in that organ, while an inverse profile was found for IFN-γ, TNF-α e IL-10 expression. These results suggest that T lymphocytes depends on iron to produce IFN-γ, TNF-α and IL-10, while iron seems to inhibit cytokine production in monocytes. So, we propose an immunoregulatory mechanism carried out by iron during L. infantum infection in humans and dogs